ANALISIS PEMBERIAN KREDIT PADA PERUSAHAAN UMUM DAERAH BPR BANK GRESIK - Divianitasya, Frida; Aslamiyah, Suaibatul (Kinerja, 2022)
Indonesian people play an active role in the world economy. Through the world of banking, all economic actors can realize national development in order to increase economic growth. Economic actors have the ability to use credit facilities provided by banking financial institutions. Therefore, analysis of credit granting procedures is important in credit granting procedures to assess whether a credit application is feasible for approval. The bank, before extending credit, is required to conduct an assessment and analysis of prospective debtors to minimize the occurrence of non-performing loans. This study aims to formulate procedures for granting credit and identify factors that cause problem loans in order to get debtors who meet the criteria of Perumda BPR Bank Gresik. This type of research is descriptive with a qualitative approach. Data analysis uses the Miles and Huberman model, namely data collection, data reduction, data presentation, and conclusion drawing. The result of this research is that the researchers found a credit analysis procedure to minimize non-performing loans used by Perumda BPR Bank Gresik. The procedure for extending credit is through credit procedural policies, verification of prospective customer data, assessing the feasibility of granting credit, credit analysis. The steps taken by Perumda BPR Bank Gresik to minimize non-performing loans are by analyzing the factors that cause non-performing loans and through credit monitoring.